Plumbagin resurrect colistin susceptible against colistin-resistant Pseudomonas aeruginosa in vitro and in vivo - Wang, Yue; Kong, Jingchun; Zhang, Xiaodong; Liu, Yan; Huang, Zeyu; Yuan, Lu; Zhang, Ying; Cao, Jianming; Chen, Lijiang; Liu, Yong; Zhou, Tieli (Frontiers in Microbiology, 2022)
The global emergence and spread of multi-drug resistant (MDR) strains is becoming increasingly worrisome due to the overuse of broad-spectrum antibiotics. Colistin, the last resort for treating MDR strains infections, has once again returned to the clinician’s choice. However, with the widespread use of colistin, colistin-resistant gram-negative bacteria (GNB) have subsequently emerged, including colistin-resistant Pseudomonas aeruginosa (COL-R PA). Therefore, available solutions are urgently needed to respond to this situation. Here, we inspiringly found that the combination of plumbagin and colistin had an efficiently inhibitory effect for colistin-resistant P. aeruginosa in vitro through checkerboard assay and time-kill assay. The combinatorial inhibition of biofilm formation was clearly demonstrated by crystal violet staining and scanning electron microscopy (SEM), and this combination can not only inhibited biofilm formation but also eradicated the mature biofilm. Erythrocytes hemolysis test showed that plumbagin has negligible hemolysis ability. In addition, the increased survival rate of Galleria mellonella (G. mellonella) larva confirmed this combination as same as effective in vivo. As for the mechanism of this combination, propidium iodide (PI) staining showed colistin combined with plumbagin could significantly change the membrane permeability, thus exerting synergistic antibacterial activity. In conclusion, the combination of plumbagin and colistin shows a prominently synergistic antibacterial effect in vitro and in vivo, providing a promising option for the therapy of COL-R PA infection.